Punjabi taliban : driving extreamism in pakistan - Mujahid, Hussain ([S.l.] : Pentagon Press, 2012)
The book unravels the truth behind the emergence of Taliban in Punjab with one chapter each on the eight divisions: Lahore, Bhawalpur, Faisalabad, Gujranwala, Multan, Dera Ghazi Khan, Sargodha and Rawalpindi of Punjab province. The book gives a detailed account of structure of radical as well as terrorist organisations, infighting among different factions and related activities. The book quotes an intelligence agency to assert that there are some 150,000 insurgents belonging to Jehadi and fundamentalist organisations active in Punjab province and draws the reader's attention to the fact that almost all fundamentalist organisations are based in Punjab and it is Punjab that provides a majority of the terrorists and suicide bombers to various organisations active in Pakistan's tribal regions, thus negates the existing hypothesis that insurgency in tribal areas is driven by indigenous groups and bolster the author's arguments regarding the presence of Taliban and other outlawed organisations in Punjab. The author states that after the US attacks on Al-Qaeda and Taliban in Afghanistan, most of the Al-Qaeda leaders took shelter in Punjab. A majority of Al-Qaeda leaders arrested in Pakistan, including Khalid Muhammad Sheikh, Abu Zubeida and Abu Khalfan, were arrested from the Punjab cities of Rawalpindi, Faisalabad and Gujarat. "Punjabi Taliban" is based on his unparalleled access into the terrorist organisations and provides a unique insight into this new phrase, in the ongoing struggle against terrorism.
Keywords: Islamic fundamentalism; Political science; Punjab (Pakistan)